The Influence of Teacher Quality, School Image, and Digital Marketing on Parents’ Decisions in Choosing SMP RK Bintang Timur Rantauprapat - Sinaga, Lasder; Widodo, Teguh; Karnawati, Tin Agustina (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Parents’ decision in selecting a junior high school is a critical process influenced by a combination of rational evaluation and perceived value. In a competitive educational landscape, understanding the key determinants of this choice is essential for school management and strategic development. Background Problems: This research was motivated by the fluctuating and recently declining enrollment rates at SMP RK Bintang Timur Rantauprapat, a private Catholic school in Labuhan Batu, North Sumatra. This trend suggested potential issues related to perceived educational quality, institutional reputation, or modern communication strategies, necessitating an empirical investigation into the primary drivers of parental preference. Novelty: While previous studies have examined these factors in urban or general school contexts, this research provides specific insights into the dynamics of parental choice for a private Catholic junior high school in a non-metropolitan Indonesian setting, integrating traditional quality indicators with contemporary digital outreach strategies. Research Methods: Employing a quantitative approach, this study surveyed 161 parents of seventh-grade students using a saturated sampling technique. Data was collected via a structured questionnaire and analyzed using multiple linear regression in SPSS version 26. Finding/Results: Teacher quality, school image, and digital marketing each have a positive and significant influence on parents’ decisions.Together, these three variables also have a significant simultaneous effect. Digital marketing emerged as the most dominant influencing variable. Conclusion: The study concludes that parents’ decisions are multidimensional. To enhance competitiveness and attractiveness, schools must adopt an integrated strategy that prioritizes effective digital marketing to build visibility and engagement, consistently cultivate a positive school image, and continuously strengthen teacher quality. This holistic approach is vital for sustaining parental trust and preference in a digital era.